Integrasi Diversifikasi Pangan Rumput Laut dalam Pembelajaran Biologi Berorientasi Kewirausahaan - Muhammad Fuad; Rahmania Rahman; Risqah Amaliah Kasman; Siti Yasya Ey Fathanah (ITEKES Permata Ilmu Maros, 2025)
Biology education plays a strategic role in equipping students not only with mastery of scientific concepts but also with 21st-century skills, including entrepreneurial mindset and environmental sustainability awareness. Challenges related to limited formal employment opportunities, the demographic dividend, as well as national agendas on the blue economy and the achievement of the Sustainable Development Goals (SDGs) demand more contextual and applicable biology learning. However, the use of marine biological resources, particularly seaweed, as a pedagogical context in entrepreneurship-oriented biology education remains limited. Therefore, this article aims to review and synthesize research findings related to the integration of seaweed-based food diversification into biology learning as a strategy for strengthening youth entrepreneurship through bioentrepreneurship and ecopreneurship approaches. This study employed a qualitative approach using a narrative review method of reputable national and international articles published between 2015 and 2025. Data were analyzed thematically to identify patterns, novelty, and research gaps. The findings indicate that entrepreneurship-oriented biology learning consistently has a positive impact on improving students’ entrepreneurial self-efficacy, attitudes, and entrepreneurial intentions, particularly through project-based learning models. Seaweed possesses strong biological, ecological, and economic potential to serve as a learning context, especially in sustainable food diversification aligned with the blue economy and the SDGs. This review concludes that integrating seaweed-based food diversification into biology education has the potential to become an innovative pedagogical approach that bridges scientific concept mastery, the strengthening of youth entrepreneurship, and the internalization of sustainability values, while also opening opportunities for future empirical research and instructional model development